Turning tumors from cold to inflamed to improve immunotherapy response. (December 2021) - Gerard, C.L.; Delyon, J.; Wicky, A.; Homicsko, K.; Cuendet, Michel A.; Michielin, O.
Graphical abstract: Highlights: New strategies to turn cold tumors into T cell-inflamed tumors are emerging, holding great promises to extend the benefits of immunotherapies in the less favorable immune phenotypes. Combining immunotherapy with a range of treatment modalities allow acting on different immune cells and improve immune response in the clinical setting. We review the current strategies to inflame cold tumors that are currently being tested in clinical trials for multiple indications. Abstract: Immune checkpoint inhibitors have revolutionized the treatment landscape for a number of cancers over the last few decades. Nevertheless, a majority of patients still do not benefit from these treatments. Such patient-specific lack of response can be predicted, in part, from the immune phenotypes present in the tumor microenvironment. We provide a perspective on options to reprogram the tumors and their microenvironment to increase the therapeutic efficacy of immunotherapies and expand their efficacy against cold tumors. Additionally, we review data from current preclinical and clinical trials aimed at testing the different therapeutic options in monotherapy or preferably in combination with checkpoint inhibitors.